Physicochemical stability of 20 mg/mL amiodarone hydrochloride oral suspension in SyrSpend® SF PH4 (liquid) - Adoum Anissa; Le Pho Viet Anh Diane; Faisant Sophie; Legendre Pauline; Lester Marie-Antoinette; Boivin Pierre-Nicolas (De Gruyter, 2022)
Amiodarone hydrochloride is a class III antiarrhythmic drug indicated for the treatment of ventricular and supraventricular tachycardias. Oral amiodarone is only available in a tablet dosage form, which is not suitable for pediatric use. The stability of amiodarone hydrochloride suspension at 5 mg/mL was assessed in SyrSpend® SF PH4 (liquid) but oral amiodarone is typically given as a loading dose of 10-15 mg/kg/day for 4-10 days and then reduced to a maintenance dose of 5 mg/kg/day, making the 20 mg/mL concentration a better option. A hospital preparation of 20 mg/mL amiodarone hydrochloride oral suspension was developed. The purpose of this study was to determine the physicochemical stability of a 20 mg/mL amiodarone hydrochloride oral multidose suspension in a commercial compounding excipient, SyrSpend® SF PH4 (liquid) at ambient temperature and under dark conditions.